Mitochondrial topoisomerase 1 inhibition induces topological DNA damage and T cell dysfunction in patients with chronic viral infection - Dang, Xindi; Cao, Dechao; Zhao, Juan; Schank, Madison; Khanal, Sushant; Nguyen, Lam Ngoc Thao; Wu, Xiao Y.; Zhang, Yi; Zhang, Jinyu; Jiang, Yong; Ning, Shunbin; Wang, Ling; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
T cells are crucial for controlling viral infections; however, the mechanisms that dampen their responses during viral infections remain incompletely understood. Here, we studied the role and mechanisms of mitochondrial topoisomerase 1 (Top1mt) inhibition in mitochondrial dysfunction and T cell dysregulation using CD4 T cells from patients infected with HCV or HIV and compared it with CD4 T cells from healthy individuals following treatment with Top1 inhibitor - camptothecin (CPT). We found that Top1mt protein levels and enzymatic activity are significantly decreased, along with Top1 cleavage complex (Top1cc) formation, in mitochondria of CD4 T cells from HCV- and HIV-infected patients. Notably, treatment of healthy CD4 T cells with CPT caused similar changes, including inhibition of Top1mt, accumulation of Top1cc in mitochondria, increase in PARP1 cleavage, and decrease in mtDNA copy numbers. These molecular changes resulted in mitochondrial dysfunction, T cell dysregulation, and programmed cell death through multiple signaling pathways, recapitulating the phenotype we detected in CD4 T cells from HCV- and HIV-infected patients. Moreover, treatment of CD4 T cells from HCV or HIV patients with CPT further increased cellular and mitochondrial reactive oxygen species (ROS) production and cell apoptosis, demonstrating a critical role for Top1 in preventing mtDNA damage and cell death. These results provide new insights into the molecular mechanisms underlying immune dysregulation during viral infection and indicate that Top1 inhibition during chronic HCV or HIV infection can induce mtDNA damage and T cell dysfunction. Thus, reconstituting Top1mt protein may restore the mtDNA topology and T cell functions in humans with chronic viral infection.